Risk Assessment and Mitigation for Unmanned Aerial Vehicles - , Osman Yazicioglu; , Oguz Borat (Archives of Current Research International, 2020)
UAVs performance is improved, in addition to GPS, they can find routes with artificial intelligence and various techniques, and can fly autonomously. The global UAV market was US$ 25.59 billion in 2018. It is estimated that the market will reach US$70.28 billion by 2029. The first three UAV manufacturers were DCL (USA), Parrot (France) and Yuneec (PRC) and are now being produced in many countries. Aircrafts are exposed to various risks: an aerodynamic stall due to inconsistent sensor readings and inadequate response, hitting a flock of geese or flying objects, pilot being unable to prevent the plane repeatedly nosediving despite following procedures. Therefore, procedures issued by aviation agency for aircraft type certification require an aircraft manufacturer (“applicant”) to demonstrate that its design complies with all applicable agency’s regulations and requirements. Safety risk management is a key component of a safety management system and involves fundamental activities such as identifying safety hazards, and assessing the risks and mitigation. Risk management is an integral component of safety management and involves some essential steps.Take into account any current mitigation measures and assess the seriousness in terms of the worst possible realistic scenario. The risk assessment considered five operational environments; remote, rural, suburban, urban, and congested. Reliability, availability, maintainability, and safety assessment are important study in the development of UAVs. This kind of study is mandatory to increase the reliability of the UAV, its availability, and to reduce repair and maintenance costs.